Dekonstruksi elemen horor dalam kumpulan cerpen Sihir Perempuan karya Intan Paramaditha - Nugroho, Ponco Adi; Widyatwati, Ken; Suryadi, M.; Anggraeni, Rezki Amelia; Baihaqy, Muhammad Rayhan (Universitas Mulawarman, 2025)
This study reveals the deconstruction of horror elements in the short story collection Sihir Perempuan by Intan Paramaditha. The elements are the monster and art-horror elements formulated in Noël Carroll's theory of horror. This research uses a deconstruction approach. The material objects are the short stories